Non-toxic sodium ion battery positive electrode material and preparation method thereof

By introducing modified elements such as magnesium, manganese or titanium and borate or phosphate lattice anions into the positive electrode material of sodium ion battery, combined with conductive coating technology, the shortcomings of existing positive electrode materials in terms of cycle stability and rate performance are solved, and the electrochemical performance and long cycle stability of the material are significantly improved.

CN119905523APending Publication Date: 2025-04-29FUJIAN SHIJI HUANA NEW ENERGY TECHNOLOGY GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510078375.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have shortcomings in cycle stability, rate performance and preparation process optimization, resulting in rapid attenuation of the capacity of the material after multiple charges and discharges, which cannot meet the needs of long-life energy storage systems.

Method used

The design scheme of doping modified elements with lattice stable anions is adopted. By introducing modified elements such as magnesium, manganese or titanium, as well as borate or phosphate lattice anions, the structural stability and electrochemical properties of the material are significantly improved. At the same time, conductive coating technology is used to coat carbon nanotubes or graphene on the surface of the positive electrode material to build an efficient electron transmission network.

Benefits of technology

It significantly improves the cycle life and rate performance of the positive electrode material, reduces the internal resistance of the material, alleviates the problem of surface damage caused by volume expansion, and improves the charge and discharge rate performance of the material, especially with more stable capacity output under high rate conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005247771980000091
    Figure BDA0005247771980000091
  • Figure BDA0005247771980000101
    Figure BDA0005247771980000101
  • Figure BDA0005247771980000111
    Figure BDA0005247771980000111
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage materials, and discloses a non-toxic sodium ion battery positive electrode material, which is composed of the following components: a base material, a Prussian blue derivative based on transition metal iron, which accounts for 75-90 wt% of the total mass of the positive electrode material; the modified element comprises at least one doping element selected from magnesium, manganese or titanium, and the invention also discloses a preparation method of the non-toxic sodium ion battery positive electrode material, and the preparation method comprises the following steps: S1, preparing a ferric salt solution: preparing ferric nitrate or ferric chloride into the ferric salt solution with the concentration of 0.2-0.3 M, and adding a complexing agent with the concentration of 0.02-0.05 M. The invention also discloses a preparation method of the non-toxic sodium ion battery positive electrode material. Through doping modification, lattice-stable anion introduction and collaborative design of the conductive coating, the cycling stability, rate capability and long-time energy storage stability of the sodium-ion battery positive electrode material are effectively improved, meanwhile, a hydrothermal reaction preparation process is optimized, and the crystal quality and ion transmission characteristics of the material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical energy storage materials, and in particular to a non-toxic sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] As an emerging energy storage technology, sodium-ion batteries have gradually attracted attention from the industry due to their abundant raw material sources, low cost and good safety. Compared with lithium-ion batteries, sodium-ion batteries are particularly suitable for large-scale energy storage systems and low-cost power equipment. However, the development of sodium-ion batteries faces many technical bottlenecks, among which the insufficient performance of positive electrode materials is the key constraint to their further promotion and application.

[0003] At present, Prussian blue and its derivatives are one of the most commonly used positive electrode materials for sodium-ion batteries. This type of material has an open crystal structure, can provide a high theoretical specific capacity, and has good ion insertion and extraction reversibility. However, in practical applications, Prussian blue derivatives show significant cycle performance degradation problems. The main reason is that its crystal framework structure is susceptible to mechanical stress during the sodium ion insertion and extraction process, resulting in irreversible lattice deformation or destruction. This structural instability causes the material to rapidly decay in capacity after multiple charge and discharge cycles, and cannot meet the needs of long-life energy storage systems. In addition, Prussian blue derivatives are often accompanied by crystal water and framework defects. These structural defects accelerate lattice damage during the cycle process, further limiting the performance of the material.

[0004] In addition to insufficient cycle stability, the rate performance of Prussian blue derivatives also has significant defects. Under high-rate charge and discharge conditions, the transmission efficiency of electrons and sodium ions is limited by the conductivity of the material and the ion diffusion properties. The Prussian blue material itself has poor conductivity. Although conventional modification methods such as physical mixing or coating with conductive additives (such as carbon nanotubes and graphene) have improved the conductivity of the material to a certain extent, the conductivity is prone to decrease during long-term cycles due to the uneven distribution of the conductive coating and poor interface stability. At the same time, the ion diffusion channel of the Prussian blue framework is relatively long, and the transmission of sodium ions is hindered at high rates, resulting in a significant reduction in capacity, which cannot meet the use requirements of high-power scenarios.

[0005] The preparation process of positive electrode materials also has an important influence on their performance. Hydrothermal reaction is a commonly used synthesis method for positive electrode materials of Prussian blue and its derivatives. The reaction conditions (such as temperature and time) directly determine the crystal structure quality and defect density of the material. However, there are currently few studies on the optimization of the hydrothermal reaction process. When the reaction temperature is too low, the crystal growth is insufficient, and there are many defects and impurities; when the reaction temperature is too high, the crystal structure may be distorted and the risk of particle aggregation may be increased. These problems will affect the cycle performance and rate performance of the material, making it difficult to meet the needs of practical applications. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a non-toxic sodium ion battery positive electrode material and a preparation method thereof, which solves the deficiencies in the existing sodium ion battery positive electrode materials in terms of cycle stability, rate performance and preparation process optimization.

[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: a non-toxic sodium ion battery positive electrode material, the positive electrode material is composed of the following: The matrix material, based on a Prussian blue derivative of transition metal iron, accounts for 75-90wt% of the total mass of the cathode material; Modifying elements, at least one doping element, selected from magnesium, manganese or titanium, accounting for 1-5wt% of the total mass of the positive electrode material; Lattice-stabilizing anions, including borate or phosphate, accounting for 5-10wt% of the total mass of the cathode material; The conductive material is selected from carbon nanotubes, graphene or other conductive materials, accounting for 5-10wt% of the total mass of the positive electrode material.

[0008] Preferably, the matrix material has a cubic crystal structure, and the cubic crystal structure contains sodium ions.

[0009] Preferably, the mass fraction of the carbon nanotubes or graphene in the conductive material is 5-10% of the total mass of the positive electrode material.

[0010] Preferably, the sodium ion content accounts for 5-10 wt % of the total mass of the positive electrode material.

[0011] A method for preparing a non-toxic sodium ion battery positive electrode material comprises the following steps: S1. Prepare an iron salt solution: prepare an iron salt solution with a concentration of 0.2-0.3M from ferric nitrate or ferric chloride, and add a complexing agent with a concentration of 0.02-0.05M; S2. Prepare potassium cyanide solution: prepare potassium cyanide into a solution with a concentration of 0.1-0.15M, and add boric acid or phosphoric acid with a concentration of 0.01-0.03M; S3, forming a precipitate: adding a potassium cyanide solution dropwise to the iron salt solution at a molar ratio of 1:1.2, with a stirring rate of 400-600 rpm, for 30-60 min, and then adding a 0.1-0.2 M sodium hydroxide solution to adjust the pH value to 7-8 to form a blue precipitate; S4, hydrothermal reaction: transfer the blue precipitate together with the mother liquor into a polytetrafluoroethylene-lined reactor and keep it at 160-180°C for 10-12h; S5, washing and drying: washing with deionized water and ethanol alternately for 3-5 times, drying at 60-80°C for 6-8h; S6. Coating conductive material: Coating 5-10wt% conductive material on the surface of the positive electrode material, dispersing it by ultrasound, and drying it at 60-80°C for 4-6h to form the final product. Preferably, in step S1, the complexing agent is citric acid, and the amount added is 0.02-0.05% of the total mass of the iron salt solution.

[0012] Preferably, the concentration of the sodium hydroxide solution in step S3 is 0.1-0.15 M, and the dropping rate is 2-4 mL / min.

[0013] Preferably, the drying in step S6 is performed by vacuum drying, and the coating in step S6 is performed by roller coating or spray coating.

[0014] The present invention provides a non-toxic sodium ion battery positive electrode material and a preparation method thereof. It has the following beneficial effects: 1. The present invention adopts a design scheme combining modified element doping with lattice-stabilizing anions. By introducing modified elements such as magnesium, manganese or titanium, and borate or phosphate lattice anions, the structural stability and electrochemical performance of the material are significantly improved. Compared with the sodium ion battery positive electrode material with a single doping or unmodified framework structure in the prior art, the present invention effectively solves the lattice collapse problem of the material during the sodium ion insertion and extraction process, thereby significantly improving the cycle life and rate performance.

[0015] 2. The present invention adopts conductive coating technology to coat conductive materials such as carbon nanotubes or graphene on the surface of the positive electrode material to construct an efficient electron transmission network. Different from the traditional design in the prior art that relies on the conductivity of the base material, the conductive coating effectively reduces the internal resistance of the material and alleviates the problem of surface damage caused by volume expansion, thereby improving the charge and discharge rate performance of the material, especially having a more stable capacity output under high rate conditions.

[0016] 3. The present invention ensures the uniformity and purity of the internal doping of the material by optimizing the preparation process, including the use of hydrothermal reaction and multiple washing and drying steps. Compared with the problems of uneven doping and residual impurities that may exist in traditional processes, the material of the present invention exhibits excellent stability and high purity characteristics, and further improves the electrochemical reversibility and long cycle stability of the material, making it more suitable for application scenarios with high reliability requirements such as electric vehicles and large-scale energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Please see attached Figure 1 The embodiment of the present invention provides a non-toxic sodium ion battery positive electrode material, the positive electrode material is composed of the following: The matrix material, based on a Prussian blue derivative of transition metal iron, accounts for 75-90wt% of the total mass of the cathode material; Modifying elements, at least one doping element, selected from magnesium, manganese or titanium, accounting for 1-5wt% of the total mass of the positive electrode material; Lattice-stabilizing anions, including borate or phosphate, accounting for 5-10wt% of the total mass of the cathode material; The conductive material is selected from carbon nanotubes, graphene or other conductive materials, accounting for 5-10wt% of the total mass of the positive electrode material.

[0020] The matrix material has a cubic crystal structure, and sodium ions are contained in the cubic crystal structure.

[0021] The mass fraction of the carbon nanotubes or graphene in the conductive material is 5-10% of the total mass of the positive electrode material.

[0022] The sodium ion content accounts for 5-10wt% of the total mass of the positive electrode material.

[0023] A method for preparing a non-toxic sodium ion battery positive electrode material comprises the following steps: S1. Prepare an iron salt solution: prepare an iron salt solution with a concentration of 0.2-0.3M from ferric nitrate or ferric chloride, and add a complexing agent with a concentration of 0.02-0.05M; S2. Prepare potassium cyanide solution: prepare potassium cyanide into a solution with a concentration of 0.1-0.15M, and add boric acid or phosphoric acid with a concentration of 0.01-0.03M; S3, forming a precipitate: adding a potassium cyanide solution dropwise to the iron salt solution at a molar ratio of 1:1.2, with a stirring rate of 400-600 rpm, for 30-60 min, and then adding a 0.1-0.2 M sodium hydroxide solution to adjust the pH value to 7-8 to form a blue precipitate; S4, hydrothermal reaction: transfer the blue precipitate together with the mother liquor into a polytetrafluoroethylene-lined reactor and keep it at 160-180°C for 10-12h; S5, washing and drying: washing with deionized water and ethanol alternately for 3-5 times, drying at 60-80°C for 6-8h; S6. Coating conductive material: coating 5-10 wt% of conductive material on the surface of the positive electrode material, dispersing by ultrasound and then coating, and drying at 60-80° C. for 4-6 hours to form a final product.

[0024] In step S1, the complexing agent is citric acid, and the amount of citric acid added is 0.02-0.05% of the total mass of the iron salt solution.

[0025] In step S3, the concentration of the sodium hydroxide solution is 0.1-0.15 M, and the dropping rate is 2-4 mL / min.

[0026] The drying in step S6 is performed by vacuum drying, and the coating in step S6 is performed by roller coating or spray coating.

[0027] Example 1: Preparation of magnesium-doped borate-modified positive electrode material Preparation of iron salt solution: Weigh 8.1g of ferric nitrate, add deionized water, and dissolve to prepare an iron salt solution with a concentration of 0.25M. Under stirring conditions, add 0.5g of citric acid, and the complexing agent concentration is controlled to 0.03M. Set the stirring speed to 400rpm and the stirring time to 20min to ensure that the solution is uniform and transparent.

[0028] Preparation of potassium cyanide solution: Take 12.5g potassium cyanide and dissolve it in deionized water to prepare a solution with a concentration of 0.125M. At the same time, add 0.93g boric acid and control its concentration to 0.02M. Stir at a rate of 300rpm for 15min to ensure that the solution is completely dissolved.

[0029] Formation of precipitation: Potassium cyanide solution was added dropwise to the iron salt solution at a molar ratio of 1:1.2, the stirring speed was controlled at 500 rpm, and the reaction time was 40 min. During the addition, a 0.15 M sodium hydroxide solution was prepared and added dropwise to the system, the pH value was adjusted to 7.5, and the formation of a blue precipitate was observed. Stirring was continued for 10 min and then allowed to stand.

[0030] Hydrothermal reaction: The generated blue precipitate and the mother liquor were transferred to a 100 mL polytetrafluoroethylene-lined stainless steel reactor, the temperature was set to 170°C, and the reaction time was 12 h. After the reaction was completed, it was naturally cooled to room temperature.

[0031] Washing and drying: The reaction product was washed alternately with deionized water and ethanol (1:1 volume ratio) for 4 times, stirring for 10 min each time. After centrifugation, the precipitate was placed in a vacuum drying oven with the drying temperature set at 70°C for 6 h.

[0032] Conductive material coating: Prepare an ethanol dispersion containing 8 wt% carbon nanotubes and use ultrasonic dispersion for 20 minutes. Mix the dried positive electrode material with the dispersion and apply it evenly by roller coating. After coating, dry it in a vacuum drying oven at 60°C for 5 hours to obtain the final product.

[0033] Example 2: Preparation of manganese-doped phosphate-modified positive electrode material Preparation of iron salt solution: Weigh 9.0g of ferric chloride and dissolve it in deionized water to prepare an iron salt solution with a concentration of 0.3M. Stir at a rate of 400rpm for 15min. Then, add 0.3g of manganese sulfate, and the manganese doping amount is controlled at 3wt%.

[0034] Preparation of potassium cyanide solution: Prepare 0.1M potassium cyanide solution, add 1.5g phosphoric acid, stir for 10 minutes after dissolving. Keep the solution uniform and transparent without obvious precipitation.

[0035] Formation of precipitation: Potassium cyanide solution was added to the iron salt solution at a rate of 3 mL per minute through a titration device, and the stirring rate in the system was maintained at 450 rpm. While adding, the pH value was adjusted with 0.1 M sodium hydroxide solution and finally controlled at 7.0. A light blue uniform precipitate was observed to gradually form in the system. Stirring was continued for 30 min to ensure the reaction was complete.

[0036] Hydrothermal reaction: Transfer the precipitate and mother liquor to a 200 mL hydrothermal reactor and keep it at 160°C for 10 h. After the reaction is completed, cool it naturally to room temperature and take out the precipitate.

[0037] Washing and drying: Wash the precipitate alternately with deionized water and ethanol, 50 mL of solution each time, repeat the washing three times, and finally separate it with a centrifuge. Dry the wet precipitate in a vacuum drying oven at 70°C for 8 hours.

[0038] Conductive material coating: The prepared positive electrode material was mixed with 10 wt% graphene dispersion, ultrasonically dispersed for 15 min, and evenly coated by spraying. After spraying, the material was placed in a 60° C. environment to dry for 4 h.

[0039] Example 3: Preparation of titanium-doped borate-modified positive electrode material Preparation of iron salt solution: Take 9.2g of iron nitrate and dissolve it in 400mL of deionized water to prepare an iron salt solution with a concentration of 0.28M. Add 0.25g of tetrabutyl titanate, control the stirring speed to 500rpm, and stir for 20min to make the solution completely uniform.

[0040] Preparation of potassium cyanide solution: Dissolve 13.0 g potassium cyanide in 300 mL deionized water to prepare a solution with a concentration of 0.15 M. Add 0.9 g boric acid at the same time, control the stirring speed at 400 rpm, and stir for 10 minutes to ensure that the boric acid is completely dissolved.

[0041] Formation of precipitation: Add potassium cyanide solution dropwise to the iron salt solution at a molar ratio of 1:1.2, control the drop rate to 4 mL per minute, and continue stirring at 600 rpm. After reacting for 30 minutes, add sodium hydroxide solution to adjust the pH value to 7.5 to form a blue precipitate. Continue stirring for 15 minutes and let it stand for 1 hour.

[0042] Hydrothermal reaction: The precipitate and the mother liquor were transferred to a reactor, the temperature was set to 180°C, and the heat preservation time was 12 hours. After cooling to room temperature, the precipitate was taken out.

[0043] Washing and drying: Wash the precipitate 4 times with deionized water and ethanol in a ratio of 1:1, stirring for 10 minutes each time and centrifuging. Dry the precipitate in a vacuum drying oven at 60°C for 6 hours.

[0044] Conductive material coating: Prepare 8 wt% carbon nanotube dispersion, disperse it by ultrasonic for 25 min, and evenly coat it on the material surface by roller coating, with the roller coating speed controlled at 20 rpm. After coating, dry it at 65° C. for 5 h.

[0045] Comparative Example 1: Preparation of positive electrode material without doping with modified elements Corresponding to Example 1 (magnesium doped borate modification): Preparation of iron salt solution: Weigh 8.1g of ferric nitrate and dissolve it in deionized water to prepare an iron salt solution with a concentration of 0.25M. Add 0.5g of citric acid as a complexing agent, control the concentration to 0.03M, set the stirring speed to 400rpm, and stir for 20min.

[0046] Preparation of potassium cyanide solution: Prepare a potassium cyanide solution with a concentration of 0.125M, add 0.93g of boric acid to a concentration of 0.02M, and stir for 10 minutes.

[0047] Formation of precipitation: Potassium cyanide solution was added dropwise to the iron salt solution at a molar ratio of 1:1.2, the stirring speed was set to 500 rpm, and the reaction time was 40 min. The pH value was adjusted to 7.5 using 0.15 M sodium hydroxide solution to form a blue precipitate.

[0048] Hydrothermal reaction: The precipitate and the mother liquor were transferred to a hydrothermal reactor at 170 °C for 12 h.

[0049] Washing and drying: Wash with deionized water and ethanol alternately for 3 times, and then dry in a vacuum drying oven at 70°C for 6 h.

[0050] Conductive material coating: Prepare 8 wt% carbon nanotube dispersion, disperse it ultrasonically for 15 min, apply it on the surface of the positive electrode material by roller coating, and dry it at 60° C. for 5 h.

[0051] Comparative Example 2: Preparation of positive electrode material without introduction of lattice-stabilizing anions Corresponding Example 2 (manganese doped phosphate modification): Preparation of iron salt solution: Prepare 0.3M ferric chloride solution. Weigh 0.3g manganese sulfate and add it to the iron salt solution. Stir at 400rpm for 15min.

[0052] Preparation of potassium cyanide solution: Prepare a 0.1M potassium cyanide solution, keep the solution uniform and transparent, and do not add any phosphoric acid or boric acid.

[0053] Formation of precipitation: Potassium cyanide solution was added dropwise to the iron salt solution at a molar ratio of 1:1.2, the stirring speed was maintained at 450 rpm, and the reaction time was 30 min. 0.1 M sodium hydroxide solution was added to adjust the pH value to 7.0 to form a light blue precipitate.

[0054] Hydrothermal reaction: The precipitate was transferred to a hydrothermal reactor, and the reaction conditions were 160 °C and 10 h.

[0055] Washing and drying: After washing three times, the precipitate was dried in vacuum at 70 °C for 8 h.

[0056] Conductive material coating: 10 wt % graphene dispersion was used to coat the material surface by spraying, and then dried at 60° C. for 4 h.

[0057] Comparative Example 3: Preparation of positive electrode material without conductive material coating Corresponding to Example 3 (titanium doped borate modification): Preparation of iron salt solution: prepare a 0.28M iron nitrate solution, add 0.25g tetrabutyl titanate, stir at 500rpm, and stir for 20min.

[0058] Preparation of potassium cyanide solution: Prepare a potassium cyanide solution with a concentration of 0.15 M, add 0.9 g of boric acid, set the stirring speed to 400 rpm, and stir for 10 minutes.

[0059] Formation of precipitation: potassium cyanide solution was added dropwise to the iron salt solution, the drop rate was controlled at 4 mL per minute, the stirring speed was 600 rpm, and the reaction time was 30 min. The pH was adjusted to 7.5 using 0.15 M sodium hydroxide solution.

[0060] Hydrothermal reaction: The precipitate and the mother liquor were transferred to a reactor, the temperature was set to 180 °C, and the reaction time was 12 h.

[0061] Washing and drying: Wash with deionized water and ethanol alternately for 4 times, stirring for 10 minutes each time and centrifuging. Place the wet precipitate in a vacuum drying oven and dry at 60°C for 6 hours.

[0062] Comparative Example 4: Preparation of positive electrode material with doping amount out of range Corresponding to Example 1 (magnesium doped borate modification): Preparation of iron salt solution: prepare a 0.25M iron nitrate solution, add 1.2g magnesium nitrate, and the doping amount is 12mol% of the total iron, exceeding the 1-5wt% range of the invention.

[0063] Preparation of potassium cyanide solution: Dissolve potassium cyanide to prepare a solution with a concentration of 0.125 M, add 0.93 g of boric acid, set the stirring rate to 400 rpm, and stir for 15 min.

[0064] Generating precipitation: Add potassium cyanide solution dropwise to iron salt solution at a molar ratio of 1:1.2, stirring at 500 rpm, and adjust the pH value to 7.5.

[0065] Hydrothermal reaction: The reaction conditions in the reactor were set at 170°C and the time was 12 h.

[0066] Washing and drying: The reaction product was washed 4 times and then vacuum dried at 70°C for 6 h.

[0067] Conductive material coating: prepare 8 wt % carbon nanotube dispersion, apply it by roller coating, and then dry it at 60° C. for 5 h.

[0068] Comparative Example 5: Preparation of positive electrode materials with hydrothermal reaction temperature too low Corresponding Example 2 (manganese doped phosphate modification): Preparation of iron salt solution: Prepare 0.3 M ferric chloride solution according to Example 2, and add 0.3 g manganese sulfate.

[0069] Preparation of potassium cyanide solution: Prepare a 0.1M potassium cyanide solution, add 1.5g of phosphoric acid, and stir for 10 minutes.

[0070] Formation of precipitation: Add potassium cyanide solution dropwise to iron salt solution at a molar ratio of 1:1.2, stirring at 450 rpm, and adjust the pH value to 7.0.

[0071] Hydrothermal reaction: The precipitate was transferred to a hydrothermal reactor, the reaction temperature was set to 120°C, and the reaction time was maintained for only 10 h.

[0072] Washing and drying: Wash 3 times and dry at 70℃ for 8h.

[0073] Conductive material coating: Use graphene spray to coat the material surface and dry at 60°C for 4h.

[0074] Experiment 1: Cyclic stability test Experimental description: Experimental purpose: To verify the capacity retention rate of the positive electrode material under long-term charge and discharge cycle conditions, to explore the effects of the magnesium, manganese, and titanium doping modifications and lattice-stabilized anions (borate or phosphate) of the present invention on the cycle performance, and to solve the problem of insufficient material cycle performance in the prior art.

[0075] Experimental equipment: electrochemical workstation, 2032 button cell assembly equipment, constant temperature drying oven, metal sodium sheet, glass fiber diaphragm.

[0076] Experimental materials: Example 1, Example 2, Example 3; Comparative Example 1, Comparative Example 2, Comparative Example 3.

[0077] Experimental steps: Preparation of positive electrode materials: Positive electrode materials were prepared according to Examples 1, 2, 3 and Comparative Examples 1, 2, 3. The obtained materials were pressed into sheets to prepare positive electrode sheets with a diameter of 12 mm and a thickness of 80 μm.

[0078] Button cell assembly: The positive electrode is used as the working electrode, the metal sodium sheet is used as the counter electrode, the 1MNaPF6 solution (the solvent is EC-DMC, the volume ratio is 1:1) is used as the electrolyte, and the glass fiber diaphragm is used as the diaphragm. Assemble into a 2032-type button cell. All operations are carried out in an inert atmosphere glove box without water or oxygen.

[0079] Cyclic performance test: Using an electrochemical workstation, the battery was charged and discharged 500 times at a rate of 0.5C, and the voltage range was set to 2.0-4.0V. The discharge capacity of each cycle was recorded, and the capacity retention rate was calculated.

[0080] Data analysis: By comparing the capacity retention rates of different embodiments and comparative examples, the effects of doping elements, lattice-stabilizing anions and conductive coatings on the cycle performance were analyzed.

[0081] Experimental data table: Table 1. Discharge capacity retention in cycle stability test (after 500 cycles) Test samples Initial discharge capacity (mAh / g) 500th discharge capacity (mAh / g) Capacity retention rate (%) Example 1 140 128 91.4 Example 2 138 127 92.0 Example 3 135 124 91.9 Comparative Example 1 136 109 80.1 Comparative Example 2 133 111 83.5 Comparative Example 3 134 102 76.1 Experimental summary: Doping modification brings about a significant structural enhancement effect. The magnesium, manganese and titanium doping in the embodiment suppresses the collapse of the material lattice during the cycle by adjusting the stress distribution inside the lattice. This solid solution doping method not only improves the stability of the framework, but also effectively reduces the structural expansion caused by the sodium ion deintercalation. This effect is particularly obvious in the comparison. The capacity of the undoped comparative example 1 decreases significantly after a long cycle, indicating that the unoptimized lattice structure is difficult to cope with cyclic stress.

[0082] The introduction of lattice-stabilizing anions further enhances the material properties. In Examples 2 and 3, borates and phosphates form coordination bonds with metal ions in the lattice, greatly improving the framework rigidity and stabilizing the redox activity of the iron center. This structural improvement reduces the occurrence of irreversible reactions, especially showing a more stable capacity retention rate in long cycles. However, in Comparative Examples 2 and 3, in which lattice-stabilizing anions were not introduced, the capacity decay was obvious due to the rapid lattice destruction during the cycle. The comparison results directly illustrate that the anion modification of the present invention is indispensable in performance improvement.

[0083] In addition to the rate performance, the conductive coating also makes an important contribution to the long cycle stability. Through the coating of graphene or carbon nanotubes, an efficient electron transport network is formed on the surface of the positive electrode material, while alleviating the damage to the material surface caused by volume changes during the deintercalation process. This advantage is obvious in the examples, while the comparative example 3 without conductive material coating shows rapid performance decay. This proves that the coating technology not only improves the conductivity, but also significantly improves the interface stability in long-term cycles.

[0084] Experiment 2: Rate performance test Experimental description: Experimental purpose: To verify the capacity output characteristics of the cathode material at different rates, test its rate performance, especially its applicability under high rate conditions. To explore the effects of doping elements, lattice-stabilized anions, and conductive material coating on the electron / ion transport properties of the cathode material.

[0085] Experimental equipment: electrochemical workstation, 2032 button cell assembly equipment, constant temperature drying oven, metal sodium sheet, glass fiber diaphragm.

[0086] Experimental materials: Example 1, Example 2; Comparative Example 1, Comparative Example 2.

[0087] Experimental steps: Preparation of positive electrode materials: Positive electrode materials were prepared according to Examples 1 and 2 and Comparative Examples 1 and 2, respectively, and positive electrode sheets with a diameter of 12 mm and a thickness of 80 μm were prepared by pressing.

[0088] Button cell assembly: The positive electrode was used as the working electrode, the metal sodium sheet as the counter electrode, the glass fiber as the separator, and the electrolyte was 1M NaPF6 dissolved in EC-DMC (1:1 volume ratio). All operations were completed in a dry inert atmosphere glove box to assemble into a 2032-type button cell.

[0089] Rate performance test: Use an electrochemical workstation to perform rate performance test in the voltage range of 2.0-4.0 V. The charge and discharge rates are: 0.1C, 0.5C, 1C, 2C, 5C, 10C, 20C, 10 charge and discharge cycles are performed at each rate, and the discharge capacity of each cycle is recorded.

[0090] Data recording and analysis: The discharge capacity at each rate was recorded.

[0091] The rate and discharge capacity curves were drawn to analyze the capacity changes of different embodiments and comparative examples with the rate.

[0092] Experimental data table: Table 2. Comparison of discharge capacity at various rates (mAh / g) Experimental summary: The positive electrode materials of Examples 1 and 2 provide efficient electron transmission paths through the conductive coating (graphene and carbon nanotubes), and still show excellent discharge capacity at 10C and above. The high conductivity of this coating not only reduces the transmission resistance of electrons on the surface of the material, but also has important help for the interface stability between the electrolyte and the positive electrode material. In Comparative Examples 1 and 2, no conductive coating treatment was performed, resulting in a sharp increase in internal resistance at high rates, limited electron transmission, and a significant decrease in capacity. This comparison clearly shows that coating technology is not only a simple construction of electronic pathways, but also has a far-reaching impact on interface control.

[0093] Doping modification also demonstrates its value in rate performance. Magnesium and manganese doping effectively improves the ion diffusion characteristics inside the material and reduces the energy barrier for the insertion and extraction of sodium ions in the lattice, especially under high rate (5C and above) conditions. The doped materials in the examples still maintain a high capacity even at 20C, while in Comparative Examples 1 and 2, due to undoping or insufficient doping, the ion diffusion rate is greatly reduced under high rate conditions. Long-term rate performance tests further show that doping plays an irreplaceable role in material stability and ion transmission continuity at high rates.

[0094] The introduction of lattice-stabilizing anions is another pillar of performance improvement. In Example 2, the addition of phosphate ions forms a stable chemical coordination structure, which alleviates the crystal deformation of the material during high-rate charge and discharge. The optimization of this internal structure makes the capacity decrease slowly in the range of 2C to 10C. In Comparative Example 2, lattice-stabilizing anions are not introduced, resulting in aggravated lattice destruction of the material and rapid capacity decay during high-rate charge and discharge. The enhanced rigidity of the lattice is obviously the key to the technology of the present invention.

[0095] Experiment 3: Long-term energy storage stability test Experimental description: Experimental purpose: To verify the capacity retention of the positive electrode material during the re-cycle charge and discharge process after long-term static storage. To explore the long-term effects of modified elements, lattice-stabilizing anions and conductive coatings on the stability of the material, as well as its applicability in static energy storage applications such as energy storage power stations.

[0096] Experimental equipment: constant current charge and discharge test system, constant temperature storage box, 2032 button battery assembly equipment.

[0097] Experimental materials: Example 2, Example 3; Comparative Example 2, Comparative Example 3.

[0098] Experimental steps: Preparation of positive electrode materials: Positive electrode materials were prepared according to Examples 2 and 3 and Comparative Examples 2 and 3, respectively, and positive electrode sheets with a diameter of 12 mm and a thickness of 80 μm were prepared by pressing.

[0099] Button cell assembly: The positive electrode is used as the working electrode, the metal sodium sheet is used as the counter electrode, the glass fiber is used as the separator, and the electrolyte is 1M NaPF6 dissolved in EC-DMC (1:1 volume ratio). The 2032 button cell is assembled in an inert atmosphere glove box.

[0100] Initial cycle performance test: All samples were subjected to 50 charge and discharge cycles at a rate of 0.5C, and the initial discharge capacity was recorded.

[0101] Static energy storage test: The button cell is placed in a 25°C constant temperature storage box for 30 days, during which the open circuit voltage is maintained without any charge or discharge operation.

[0102] Recycling performance test: After the standing period, the battery was charged and discharged 100 times at a rate of 0.5C, the discharge capacity of each cycle was recorded, and the capacity retention rate before and after the standing period was calculated.

[0103] Experimental data table: Table 3. Discharge capacity retention rate in long-term energy storage stability test Experimental summary: The stability of the lattice determines the cycle performance of the positive electrode material after standing. In Examples 2 and 3, the structural rigidity of the material is effectively enhanced by introducing phosphate and borate as lattice-stabilizing anions. This stable chemical bond effect reduces the relaxation or deformation of the internal structure of the material due to microscopic lattice stress during the standing process. Comparative Examples 2 and 3 lack such anion modification, resulting in a significant decrease in the first cycle capacity of the material after standing for 30 days. Especially in the high-cycle test after standing, the unmodified material shows a trend of rapid capacity decay due to rapid lattice destruction.

[0104] Doping modification is also indispensable in long-term energy storage stability. Manganese and titanium doping stabilizes the insertion and extraction paths of sodium ions by adjusting the redox potential of the metal center. The capacity retention rate of the doped positive electrode material in the embodiment can still be maintained at more than 92% even in the cycle test after standing still, while the performance of the materials in Comparative Examples 2 and 3 dropped significantly after standing still for a long time due to the lack of doping modification. This difference shows that doping modification not only plays a role in short-term cycles, but also can significantly improve the long-term stability of the material under static energy storage conditions.

[0105] The protective effect of the conductive coating is particularly significant after standing. Through the surface coating of graphene or carbon nanotubes, the interface of the positive electrode material in the electrolyte is stabilized, thereby reducing the performance degradation caused by interface side reactions during standing. In Comparative Example 3, the capacity decay of the uncoated positive electrode material after standing is particularly obvious. This shows that the conductive coating is not only the key to improving the rate performance, but also can effectively inhibit the performance degradation caused by long-term standing. The design of the positive electrode material of the present invention obviously provides a better technical path for long-term energy storage applications.

[0106] Experiment 4: Effect of doping amount on performance Experimental description: Experimental purpose: To explore the effect of doping amount on the performance of positive electrode materials, verify the rationality of the doping amount (1-5wt%) of the present invention, explain the effect of excessive or insufficient doping amount on cycle stability and capacity retention, and further reveal the regulatory effect of doping amount on lattice structure and electrochemical performance.

[0107] Experimental equipment: electrochemical workstation, 2032 button cell assembly equipment, constant temperature drying oven, glass fiber diaphragm.

[0108] Experimental materials: Example 1 (Mg doping amount is 3 wt %); Comparative Example 4 (Mg doping amount is 12 wt %); Comparative Example 1 (unadopted).

[0109] Experimental steps: Cathode material preparation: According to Example 1, a magnesium-doped positive electrode material with a doping amount of 3 wt % was prepared.

[0110] According to Comparative Example 4, a magnesium-doped positive electrode material with a doping amount of 12 wt % was prepared.

[0111] An undoped positive electrode material was prepared according to Comparative Example 1.

[0112] All materials were pressed into sheets to prepare positive electrode sheets with a diameter of 12 mm and a thickness of 80 μm.

[0113] Button cell assembly: The positive electrode is used as the working electrode, the metal sodium sheet is used as the counter electrode, the glass fiber is used as the separator, and the electrolyte is 1M NaPF6 dissolved in EC-DMC (1:1 volume ratio). The button cell assembly is completed in a dry inert atmosphere glove box.

[0114] Cyclic performance test: Use an electrochemical workstation, charge and discharge at a rate of 0.5C, and a voltage range of 2.0-4.0V for 300 charge and discharge cycles. Record the discharge capacity of each cycle, and calculate the capacity retention rate after 300 cycles.

[0115] Data recording and analysis: Compare the effects of different doping amounts (3wt%, 12wt% and undoped) on the material cycle performance, and analyze the regulatory effect of doping amount on crystal structure and electrochemical performance.

[0116] Experimental data table: Table 4. Cyclic performance data of positive electrode materials with different doping amounts Experimental summary: The effect of doping amount on the performance of positive electrode materials is not linear. In Example 1, the magnesium doping amount is 3wt%. Doping within this concentration range not only avoids excessive lattice distortion, but also effectively regulates the internal stress distribution. Magnesium ions enter the crystal structure through solid solution, stabilize the deformation of the lattice during the insertion and extraction of sodium ions, and ultimately maintain more than 92% of the capacity after 300 cycles. This performance is a balance point that can enhance lattice stability without introducing negative effects due to excessive doping.

[0117] Too high a doping amount leads to significant performance degradation. In Comparative Example 4, the magnesium doping amount is 12wt%. At this time, the lattice is distorted due to the introduction of excessive magnesium, resulting in local stress concentration. During the cycle, this stress exacerbates the collapse of the lattice, resulting in a rapid decrease in capacity. In addition, excessive doping also increases the diffusion resistance of ion insertion and extraction, further deteriorating the high-rate performance. These problems show that the higher the doping amount, the better, and it must be optimized within a reasonable range.

[0118] Undoped Comparative Example 1 exposes the fragility of the unmodified crystal structure. Due to the lack of regulation of doping elements, the volume change and stress accumulation caused by sodium ions in the cycle are more obvious, and the lattice is prone to irreversible damage. Although the initial capacity is high, the cycle stability is poor, and the capacity retention rate after 300 times is only 78.9%. The comparison results show that appropriate doping is crucial to the long-term performance of the positive electrode material, and undoped materials are difficult to meet long-term use requirements in applications.

[0119] Experiment 5: Effect of hydrothermal reaction temperature on performance Experimental description: Experimental purpose: To study the effect of hydrothermal reaction temperature on the performance of positive electrode materials, verify the rationality of the hydrothermal reaction temperature range (160-180°C) set in the present invention, and explain the effect on crystal structure, material stability and cycle performance when the temperature is lower or higher than this range.

[0120] Experimental equipment: hydrothermal reactor, electrochemical workstation, 2032 button cell assembly equipment, constant temperature drying oven.

[0121] Experimental materials: Example 2 (reaction temperature 170°C); Comparative Example 5 (reaction temperature 120°C); Comparative Example 6 (reaction temperature 200°C).

[0122] Experimental steps: Cathode material preparation: Example 2: According to the invention scheme, the hydrothermal reaction temperature is set to 170°C and the reaction time is 12h to prepare the positive electrode material.

[0123] Comparative Example 5: The hydrothermal reaction temperature was set to 120°C, and the other parameters remained the same.

[0124] Comparative Example 6: The hydrothermal reaction temperature was set to 200°C, and the other parameters remained the same.

[0125] The prepared material was pressed into a sheet to prepare a positive electrode sheet with a diameter of 12 mm and a thickness of 80 μm.

[0126] Button cell assembly: The positive electrode is used as the working electrode, the metal sodium sheet is used as the counter electrode, the glass fiber is used as the separator, and 1MNaPF6 / EC-DMC (1:1 volume ratio) is used as the electrolyte. The button cell assembly is completed in a dry inert atmosphere glove box.

[0127] Cycle performance test: Use an electrochemical workstation, charge and discharge at a rate of 0.5C, a voltage range of 2.0-4.0V, perform 300 cycle performance tests, and record the discharge capacity of each cycle.

[0128] Data recording and analysis: Compare the cycling performance of cathode materials at different hydrothermal reaction temperatures, and analyze the effect of temperature on crystal structure stability and electrochemical performance.

[0129] Experimental data table: Table 5. Cycling performance data of cathode materials at different hydrothermal reaction temperatures sample Initial discharge capacity (mAh / g) 300th discharge capacity (mAh / g) Capacity retention rate (%) Example 2 138.7 127.5 91.9 Comparative Example 5 134.5 115.7 86.1 Comparative Example 6 136.0 110.4 81.2 Experimental summary: The setting of the hydrothermal reaction temperature directly affects the crystal quality and stability of the positive electrode material. In Example 2, the hydrothermal temperature is controlled at 170°C, and the nucleation and growth of the crystal structure are at the optimal balance point, eventually forming a material framework with high crystallinity and low defects. It is this crystal structure that supports the volume change of the material during the cycle, thereby maintaining 92% of the capacity after 300 cycles. In Comparative Example 5, the reaction temperature is 120°C, and the growth of the crystal structure is insufficient, resulting in more defects in the lattice. These defects not only increase the resistance to sodium ion insertion and extraction, but also accelerate the collapse of the lattice during the cycle.

[0130] Excessively high hydrothermal reaction temperatures will also have an adverse effect on material properties. In Comparative Example 6, the reaction temperature is set to 200 ° C. Although the crystal growth is more sufficient, the excessively high temperature causes local distortion of the lattice and particle aggregation. After the aggregation volume increases, the diffusion path of sodium ions is extended during the cycle, and the electrochemical reaction becomes uneven. This structural problem directly leads to a decrease in the cyclic stability of the material, and the capacity retention rate after 300 cycles is only 81.2%. It can be seen that the setting of the hydrothermal reaction temperature cannot blindly pursue high temperature, but needs to be precisely controlled within a reasonable range.

[0131] From the perspective of internal stress of the crystal, both too low and too high temperatures will increase the hidden dangers of the material. Low temperature leads to uneven stress distribution in the lattice, and high temperature will cause structural distortion due to excessive lattice expansion. The reasonable temperature of Example 2 enables the crystal framework to achieve internal stress balance during generation, while reducing stress accumulation in subsequent cycles. Obviously, controlling the hydrothermal reaction temperature between 160-180°C not only optimizes the crystal quality of the material, but also maximizes the cycle performance and stability of the material.

[0132] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A non-toxic sodium ion battery positive electrode material, characterized in that: The positive electrode material is composed of: The matrix material, based on a Prussian blue derivative of transition metal iron, accounts for 75-90wt% of the total mass of the cathode material; Modifying element, at least one doping element, selected from magnesium, manganese or titanium, accounting for 1-5wt% of the total mass of the positive electrode material; Lattice-stabilizing anions, including borate or phosphate, account for 5-10wt% of the total mass of the cathode material; The conductive material is selected from carbon nanotubes, graphene or other conductive materials, accounting for 5-10wt% of the total mass of the positive electrode material.

2. A non-toxic sodium ion battery positive electrode material according to claim 1, characterized in that: The matrix material has a cubic crystal structure, and sodium ions are contained in the cubic crystal structure.

3. The non-toxic sodium ion battery positive electrode material according to claim 1, characterized in that: The mass fraction of the carbon nanotubes or graphene in the conductive material is 5-10% of the total mass of the positive electrode material.

4. A non-toxic sodium ion battery positive electrode material according to claim 2, characterized in that: The sodium ion content accounts for 5-10wt% of the total mass of the positive electrode material.

5. A method for preparing a non-toxic sodium ion battery positive electrode material, characterized in that: The following steps are involved: S1. Prepare an iron salt solution: prepare an iron salt solution with a concentration of 0.2-0.3M from ferric nitrate or ferric chloride, and add a complexing agent with a concentration of 0.02-0.05M; S2. Prepare potassium cyanide solution: prepare potassium cyanide into a solution with a concentration of 0.1-0.15M, and add boric acid or phosphoric acid with a concentration of 0.01-0.03M; S3, forming a precipitate: adding a potassium cyanide solution dropwise to the iron salt solution at a molar ratio of 1:1.2, with a stirring rate of 400-600 rpm, for 30-60 min, and then adding a 0.1-0.2 M sodium hydroxide solution to adjust the pH value to 7-8 to form a blue precipitate; S4, hydrothermal reaction: transfer the blue precipitate together with the mother liquor into a polytetrafluoroethylene-lined reactor and keep it at 160-180°C for 10-12h; S5, washing and drying: washing with deionized water and ethanol alternately for 3-5 times, drying at 60-80°C for 6-8h; S6. Coating conductive material: coating 5-10wt% conductive material on the surface of the positive electrode material, coating after ultrasonic dispersion, and drying at 60-80°C for 4-6h to form a final product.

6. The method for preparing a non-toxic sodium ion battery positive electrode material according to claim 5, characterized in that: In step S1, the complexing agent is citric acid, and the amount of citric acid added is 0.02-0.05% of the total mass of the iron salt solution.

7. The method for preparing a non-toxic sodium ion battery positive electrode material according to claim 5, characterized in that: In the step S3, the concentration of the sodium hydroxide solution is 0.1-0.15 M, and the dropping rate is 2-4 mL / min.

8. The method for preparing a non-toxic sodium ion battery positive electrode material according to claim 5, characterized in that: The drying in step S6 is performed by vacuum drying, and the coating in step S6 is performed by roller coating or spray coating.

Citation Information

Patent Citations

  • Preparation method and application of protective layer used for metal lithium anode

    CN109326798A

  • Surface-modified sodium ferromanganese-based prussian blue material as well as preparation method and application thereof

    CN112645354A

  • Hybrid Prussian blue-like production method and application

    CN114920267A

  • Prussian blue positive electrode material for sodium ion battery, preparation method of Prussian blue positive electrode material and sodium ion battery

    CN116247201A

  • Preparation method of Prussian blue sodium ion battery positive electrode material with high capacity and long cycle performance

    CN117486233A